Exploratory Sequential Analysis on the Factors Affecting the Leadership of Women in Local Governments - Ronel Geraldizo Dagohoy; Mervin G. Gascon (Changing Societies & Personalities, 2025)
Inclusive governance fosters opportunities for women to contribute to societal advancement by serving in government roles. This paper explores the factors influencing women’s leadership within the context of local government. To achieve this objective, an exploratory sequential mixed-methods design was employed, with a particular focus on Exploratory Factor Analysis. Data were collected from women employees in second-level, permanent positions among the local government units in the Province of Davao del Norte, Philippines. The findings revealed five key factors influencing women’s leadership: empowering leadership, leadership challenges, leadership motivation, leadership development support, and effective leadership communication. These factors offer valuable insights into how to advance women’s leadership, thereby promoting an inclusive environment and enhancing public service delivery. By understanding and addressing these factors, policymakers and local government authorities can create more supportive and empowering conditions for women leaders, eventually leading to more effective and equitable governance.